Database and Expert Systems Applications : 31st International Conference, DEXA 2020, Bratislava, Czech Republic, September 14–17, 2020 Proceedings /: 31st International Conference, DEXA 2020, Bratislava, Czech Republic, September 14–17, 2020 Proceedings. (2020) - Unknown
No abstract available